Role of Communication, Professionalism, and Clinical Care Skills of Postgraduate Students on Patients Recall Visits in Dental School—An Observational Study - Mohan Kumar Pasupuleti; Gautami Subhadra Penmetsa; Meghana Gangolu; Santosh Venkata Ramesh Konathala; Sruthima Naga Venkata Satya (Journal of Patient Experience, 2020)
Preservation of periodontal health after periodontal therapy is paramount for the complete elimination of periodontal diseases. In most of the Dental Schools, recall appointments are considerably low, and in particular, to the Department of Periodontics, the compliance to recall visits by the patients diagnosed with periodontal disease is still inadequate. Faculty from the Department of Periodontics framed new criteria to follow in the comprehensive clinics by the postgraduate students. The criteria include communication, intraoral examination skills, and professionalism toward dental patients. Faculty in each comprehensive dental clinic observed the clinical encounters of postgraduate students with patients and provided the feedback. The study conducted from May 2018 to April 2019, and the patients attended were 1164 of 1544. Unattended patients were 380 of 1544. Effective evaluation of the feedback provided by faculty and communication with both the postgraduate students and unattended patients resulted in further improvement in recall, that is, 151 of 380 patients. Reframed criteria, direct observation of the postgraduate students by faculty during patients interaction, assessment of feedback forms, and immediately modifying the student’s way of communication allowed maximum recall visits to the Department of Periodontics.